2021
DOI: 10.3390/en14061778
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Verified Flow Distribution Model for a Composite Modelling System

Abstract: Requirements of modern process and power technologies for compact and highly efficient equipment for transferring large heat fluxes lead to designing these apparatuses as dense parallel flow systems, ranging from conventional to minichannel dimensions according to the specific industrial application. To avoid operating issues in such complex equipment, it is vital to identify not only the local distribution of heat flux in individual parts of the heat transfer surface but also the uniformity of fluid flow dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…It was first proposed by Tuckerman and Pease in 1981 [4], and it has been shown that micro/mini-channel cooling has gained much attention for its promising capability to remove high heat flux [5][6][7]. A significant amount of research has been dedicated to micro-channel transport on four aspects: (1) simple geometry of channels [8], (2) properties of coolants [9][10][11], (3) optimization of geometries [12,13], and (4) some research methods conducted by experimental research, numerical simulation, and empirical formula.…”
Section: Introductionmentioning
confidence: 99%
“…It was first proposed by Tuckerman and Pease in 1981 [4], and it has been shown that micro/mini-channel cooling has gained much attention for its promising capability to remove high heat flux [5][6][7]. A significant amount of research has been dedicated to micro-channel transport on four aspects: (1) simple geometry of channels [8], (2) properties of coolants [9][10][11], (3) optimization of geometries [12,13], and (4) some research methods conducted by experimental research, numerical simulation, and empirical formula.…”
Section: Introductionmentioning
confidence: 99%